Evaluation of motivation system in Health Care Organization - perception of employees. A case study analysis from Polish hospital - Beck-Krala, Ewa; Tarczoń, Elżbieta (Managerial Economics, 2014)
The article concerns the evaluation of motivation system in the Health Care Sector in Poland. Using the modified Nadler and Lawler questionnaire, the effectiveness of motivation system and the employee satisfaction level is tested in one of the Malopolska Hospital in Krakow. The results of the study indicate that there is lack of critical failures in the design of the motivational system. However, the employees' expectations are met on a very low level, which means, that the motivation system is rather ineffective.